Penggunaan Media Sosial oleh Advokat Ditinjau dari Kode Etik Advokat: Studi Literatur - Fadli Fadli; Maryulianto Maryulianto (CV. ALIM'SPUBLISHING, 2026)
The development of information technology has transformed the way advocates interact with the public. Social media is used not only as a means of communication but also as a medium for legal education, personal branding, and promotion of legal services. This situation has given rise to debate regarding the ethical limits of social media use by advocates based on the Indonesian Advocates' Code of Ethics. This study aims to analyze social media use by advocates from the perspective of the professional code of ethics through a literature study approach. The method used is a literature review of various scientific articles, laws and regulations, and ethical code documents published in the last five to ten years. The results of the study indicate that the use of social media by advocates is, in principle, permissible as long as it is used for legal education, information dissemination, and professional communication. However, excessive use of social media for promotional purposes, revealing the identity or confidentiality of clients, guaranteeing victory in cases, or attacking others constitutes a violation of the principle of professional honor. Therefore, a clearer interpretation of the provisions of the code of ethics is needed to accommodate developments in digital technology without compromising the values ​​of advocate professionalism.